Nonmotor Symptoms in Parkinson's Disease - Akbar, Umer; D'Abreu, Anelyssa; Friedman, Joseph H. (Seminars in Neurology, 2017)
Nonmotor symptoms (NMSs) in Parkinson's disease (PD) have become increasingly recognized as major determinants of quality of life across cultures worldwide. Behavioral symptoms include dementia, depression, anxiety, apathy, and fatigue. Somatic symptoms include hypotension, constipation, diaphoresis, and pain. However, somatic symptoms may also be intrinsic, such as dementia, and iatrogenic, such as compulsive disorders. The authors address some of the more common disorders, yet few have been the target of clinical trials.
Keywords: nonmotor symptoms; Parkinson's disease; fatigue; dementia; psychosis